PENGARUH RETURN ON EQUITY ( ROE ), RETURN ON ASSETS (ROA), DAN NET INTEREST MARGIN (NIM) TERHADAP HARGA SAHAM PADA PT BANK CENTRAL ASIA PERIODE 2015-2024 - Indah Vebriany (PT. Hasba Edukasi Mandiri, 2026)
This study aims to determine the effect of Return On Equity (ROE) Return On Assets (ROA), and Net Interest Margin (NIM) on stock prices at PT Bank Central Asia Tbk for the period 2015-2024. The method used in this study is quantitative descriptive with secondary data in the form of the company's annual financial reports and the methods used to analyze in this study include: Classical Assumption Test (Normality, Multicollinearity, Heteroscedasticity and Autocorrelation) Multiple Linear Regression Test, Determination Coefficient test, t Test (Partial) and f test (Simultaneous) with the help of SPSS software version 31. the results of this study indicate that Return On Equity (ROE) partially does not have a significant effect on stock prices with a sig. value of 0.701>0.05, ROA does not have a significant effect on stock prices with a sig. value of 0.583>0.05, and NIM has a significant effect on Stock Prices with a sig. value. 0.028 <0.05. Simultaneously, ROE, ROA, and NIM significantly influence stock prices with a sig. 0.031 <0.05. Thus, it can be concluded that only NIM is proven to have a partial significant effect, while ROE and ROA do not. However, all three variables together significantly influence the stock price of PT Bank Central Asia Tbk.